PRAGMATIC FUNCTIONS OF ELLIPTICAL SENTENCES IN DIALOGIC SPEECH AND THEIR TRANSLATION CHALLENGES: A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK - Artikova Nodirabegim (International Journal of Literature and Language Studies, 2026)
This article examines the pragmatic functions of elliptical sentences in dialogic speech and the challenges associated with their translation between English and Uzbek. The study identifies key pragmatic functions including illocutionary force expression, speech act performance, politeness strategies, emotional expression, and dialogic cooperation. Through comparative analysis of dialogic utterances in both languages, the paper explores translation strategies and their effectiveness in preserving pragmatic equivalence. The research reveals that while English and Uzbek share similar structural patterns in elliptical constructions, Uzbek elliptical sentences often carry deeper cultural, religious, and emotional connotations. The study proposes a framework for selecting appropriate translation strategies based on text type, target audience, and translation purpose. The findings contribute to cross-cultural pragmatics and translation studies, offering practical recommendations for translators and language educators.